The effect of concurrent high intensity low volume with supplemental low intensity high volume resistance training on salivary cortisol and testosterone levels in elite athletes - Coates, T. S.; Fell, J. W.; Myers, S. A.; Bootes, M. R.; Wu, S. S. X. (Journal of Australian Strength and Conditioning, 2018)
Practitioners should be aware of large hormonal variance between individuals in response to resistance exercise and monitoring of individual hormonal responses may be required to assess the effectiveness of interventions on individual athletes.